Augmented reality in computer systems integrated with project-based learning in vocational schools - Sugihartini, Nyoman; Swisnandy, I Gusti Agung Michael (Indonesian Journal of Educational Development (IJED), 2025)
The development of technology and the demands of 21st-century skills require innovative learning that enhances student engagement and learning outcomes, particularly in Vocational High Schools (VHS). This study aims to examine the effectiveness of Augmented Reality (AR) media integrated with Project-Based Learning (PjBL) in improving student learning outcomes in computer systems at vocational high schools. A quasi-experimental method with a posttest-only control group design was employed, involving three groups: the experimental class (AR with PjBL), control group 1 (AR only), and control group 2 (conventional learning), each consisting of 38 students. Data collection techniques included learning outcome tests and documentation. The research instrument used was a standardized essay test to measure students' understanding of computer systems. Data were analyzed using one-way ANOVA, which indicated significant differences among the groups. Post hoc Tukey tests revealed that the experimental group achieved significantly higher learning outcomes than both control groups. These findings suggest that the integration of AR and PjBL creates a more contextual, interactive, and meaningful learning experience. The study supports constructivist theory and active learning as effective approaches in technology-based VHS.